2021
DOI: 10.3390/jcm10071432
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Late Postural Complications in Breast Cancer Patients Undergoing Breast-Conserving Therapy in Relation to the Type of Axillary Intervention-Cross-Sectional Study

Abstract: Purpose: The aim of the study was to evaluate posture in patients undergoing breast-conserving therapy (BCT) in relation to the type of surgical intervention to the axilla. Methods: The study was conducted on patients who had undergone breast-conserving surgical treatment for breast cancer 5–6 years earlier. In 54 patients, BCT+ALND (axillary lymph node dissection) was performed, while 63 patients were subjected to BCT+SLND (sentinel lymph node dissection). The control group consisted of 54 females. The study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
(41 reference statements)
0
4
0
Order By: Relevance
“…Moiré topography is a method that allows for the precise analysis of the locations of individual body segments (e.g., spine, shoulder girdle, and hip girdle) in relation to the body’s main axis in three planes. Because of its high accuracy, MT has been widely recognized as a gold-standard research tool to study the body postures of women who have had mastectomies [ 19 , 20 , 21 , 23 , 24 , 29 , 33 , 35 , 36 , 38 , 39 ]. The results of the above studies report the occurrence of body posture disorders in women following mastectomies, particularly in the sagittal plane [ 10 , 19 , 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Moiré topography is a method that allows for the precise analysis of the locations of individual body segments (e.g., spine, shoulder girdle, and hip girdle) in relation to the body’s main axis in three planes. Because of its high accuracy, MT has been widely recognized as a gold-standard research tool to study the body postures of women who have had mastectomies [ 19 , 20 , 21 , 23 , 24 , 29 , 33 , 35 , 36 , 38 , 39 ]. The results of the above studies report the occurrence of body posture disorders in women following mastectomies, particularly in the sagittal plane [ 10 , 19 , 24 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among the recently discussed breast cancer issues is the postural control assessment in women after mastectomy [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. A review of the above-mentioned publications indicated that the undertaken research was concerned with the impact of mastectomy on body static conditions [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ] and body posture of women who had received mastectomies [ 7 , 10 , 18 , 19 ,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations